SOME FACTORS TO BE BLAMED OR WHAT? EFL LEARNERS DIFFICULTIES IN CONSTRUCTING ENGLISH SENTENCE - Hijjatul Qamariah; Rizka Marlisa Aini (Sekolah Tinggi Pariwisata Mataram, 2021)
This is a qualitative study investigating EFL learners’ difficulties in constructing English sentence patterns. EFL learners have difficulties in constructing English sentences because of some reasons. To know what difficulties that EFL learners experienced, 30 secondary school students of X MIPA (Natural Science Program) and X IPS (Social Science Program) were selected as the participant of the research. The age ranges of the students are 15-16 years olds. The interview was used as the main data collection instrument. The result showed that there were five themes elicited from the interview data. Those are, vocabulary is the main problem, Word order is important to learn, Interlanguage is another important issue, Example-based teaching is preferred, and integrated grammar with other skills. Freon the research findings it is also indicated that there are many factors that caused learners’ grammar mastery levels. None of those factors can be judged to affect deeply than others. On the teaching side, teachers’ understanding of the needs of the learners is important. Providing better and appropriate input while teaching should not also be taken for granted by the English language teacher, assigning proper activities and feedback probably can add comprehensible input for the learner in learning grammar. On the learning side, however, learners should know their needs and better learning strategies. Some strategies are working very well for some learners, but not for others because inappropriate learning strategies can lead to an ineffective learning process. Keywords: EFL learner, learners’ difficulties, English sentence pattern